Hubungan Jiwa Kewirausahaan dengan Keberhasilan Usaha Hidroponik di Kota Kendari - Firman Purnama; Yusna Indarsyih; Fahria Nadiryati Sadimantara (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims to determine the relationship between the entrepreneurial spirit and the success of hydroponic business in Kendari City. This research was conducted in June-July 2021. The population in this study were 24 hydroponic business actors, using the saturated sampling method so that the research sample was the same as the total population. Using descriptive statistical analysis through a Likert scale measuring instrument and Spearman Rank correlation using SPSS. The results showed that the Spearman Rank correlation analysis of all entrepreneurial spirits was significantly related to moderate to strong levels of hydroponic business actors in Kendari City. Each variable is positively related at the 0.01 level of significance. The highest correlation value is owned by the relationship between daring to take risks and business growth with a score of 0.818 and is included in the very strong category.